The Malolos Aquatecture Park an aquaculture-centric complex promoting the local fish industry and livelihood of Malolos - Gollayan, Harwen Hardie F.; Sharon S. Perion (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Malolos City is the capital city of Bulacan, Philippines, and is dominated by agriculture and fisheries in terms of its industries. Malolos, according to its local framework plan, aims to widen its reach and boost its economy through these different sectors. Despite being second to Pampanga in terms of fish exports in the country, Bulacan still recorded a steady decline in its fish production. Taking the challenge of boosting the city’s fishery livelihood, the Malolos Aquatecture Park is a complex which is centered on aquaculture and its entire process. It provides livelihood training for the fishpond operators; a fishpond area in which the cultured fish can be used or consumed in the different parts of the complex; a market and dining place; and a fish processing component in which the cultured fish could be turned into packed goods ready for consumption or for export.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Aquatic resources -- Malolos City (Bulacan).; Fisheries -- Malolos City (Bulacan).; Malolos Aquatecture Park